Bearing capacity of concentric anchorage zones in post-tensioned members: A stress field solution. (April 2023) - Lei, Haipeng; Liu, Zhao; Alsomiri, Mujahed
Highlights: An alternative bearing capacity formula for post-tensioned anchorage zones is presented based on stress field approaches The stress fields consist of nodal subfields, fan subfields, and distributed tensile subfields. The proposed solution allows for both confinements by the bearing plate and the bursting reinforcement. Abstract: The post-tensioned anchorage zones are generally subdivided into local and general zones, which are treated with semi-empirical approaches and strut-and-tie models separately in many design codes. Even with their functions that look different, the two adjacent zones are intrinsically related in terms of the compression dispersion mechanism. Holding this view, this paper intends to present a mechanical model to integrate their combined actions. Firstly, two confinement effects in anchorage zones are studied: the local confinement under the bearing plate and the passive confinement by bursting reinforcement. Then, a discontinuous stress field model for concentric anchorage zones is proposed, which allows for a triaxial state of compression stresses in the local zone and the contribution of bursting reinforcement in the general zone simultaneously. After that, an explicit bearing capacity formula for anchorage zones is derived, in which the ultimate failure can be attributed to either the yielding of the distributed tension subfield or the crushing of fan subfields. The prediction of bearing capacity is in fairly good agreement with the collected test results.